Analysis Of Compliance With SAK ETAP Implementation In The Preparation Of Financial Statements KSPPS BMT Rumah Elsyarif - Nurul Maghfiroh; Wasti Reviandani (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study analyzes the application of the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in the financial statements of KSPPS BMT Rumah Elsyarif. This research uses a descriptive qualitative approach with primary data from interviews and observations, as well as secondary data in the form of financial reports in 2023. Analysis was carried out descriptively and comparatively, with validity testing through member checks. The results showed that the cooperative's financial records were accrual-based, but the recognition, measurement, and presentation of financial statements were not fully in accordance with SAK ETAP, with a level of conformity of only 43%. The financial statements presented are limited to the income statement and balance sheet, and are still simple. The main obstacles are the limited knowledge of administrative staff, lack of training, and low understanding of SAK ETAP. Efforts are needed to improve the quality of reporting through training, socialization, and adjusting the reporting system to comply with SAK ETAP. This is important to create reports that are accurate, transparent and support better decision-making